2014
DOI: 10.1007/s00330-014-3432-2
|View full text |Cite
|
Sign up to set email alerts
|

Lung MRI of invasive fungal infection at 3 Tesla: evaluation of five different pulse sequences and comparison with multidetector computed tomography (MDCT)

Abstract: • A radiation-free radiological method is desirable for assessing pulmonary infectious lesions • MRI at 3 T can depict lung infiltrates with good concordance to MDCT • SPAIR and e-THRIVE are favourable sequences for the detection of pulmonary lesions • The greatest benefit is for the diagnosis of lesions larger than 5 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 22 publications
(23 reference statements)
0
11
0
3
Order By: Relevance
“…In a study by Attenberger et al (18), pulmonary abnormalities were detected with a sensitivity of 82.3%, specificity of 78.6%, and an overall accuracy of 88% in neutropenic patients with AML using 3.0 T MRI. In another study performed with 3.0 T MRI, pulmonary lesions were detected with a high accuracy compared with MDCT in patients with invasive fungal infection (20). In the current study, CT slices were taken at a thickness of 1.25 mm, and evaluations were performed using three separate MRI sequences.…”
Section: Discussionmentioning
confidence: 90%
“…In a study by Attenberger et al (18), pulmonary abnormalities were detected with a sensitivity of 82.3%, specificity of 78.6%, and an overall accuracy of 88% in neutropenic patients with AML using 3.0 T MRI. In another study performed with 3.0 T MRI, pulmonary lesions were detected with a high accuracy compared with MDCT in patients with invasive fungal infection (20). In the current study, CT slices were taken at a thickness of 1.25 mm, and evaluations were performed using three separate MRI sequences.…”
Section: Discussionmentioning
confidence: 90%
“…In a recent study, Yan et al. found that the overall lesion‐related sensitivity of 3‐Tesla MRI was superior to that of HRCT (90.5% vs 86.9%) in detecting invasive fungal lung infection. However, Blum et al.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was designed to evaluate MRI performance to investigate pulmonary fungal diseases, compared to high-resolution CT. In a recent study, Yan et al [18] found that the overall lesion-related sensitivity of 3-Tesla MRI was superior to that of HRCT (90.5% vs 86.9%) in detecting invasive fungal lung infection. However, Blum et al [19] reported that MRI was less sensitive than HRCT in the detection of initial signs of angioinvasive aspergillosis (ie halo sign).…”
Section: Discussionmentioning
confidence: 99%
“…Ozcan et al demonstrated that using a radial acquisition method (i.e., BLADE sequence) a higher sensitivity for nodules, ground-glass opacities and consolidation, compared to half-Fourier acquisition single-shot turbo spin-echo, volumetric interpolated breath-hold examination and Fast low angle shot magnetic resonance imaging [140] can be achieved and spectral adiabatic inversion recovery and high resolution isotropic volume examination after contrast are suitable for the evaluation of invasive fungal infection [141]. Moreover, other useful tools such as intravoxel incoherent motion-derived parameters and apparent diffusion coefficient, can be applied for diagnostic purposes, allowing for example the prediction of the treatment response to fungal infection [142].…”
Section: Magnetic Resonance Imaging (Mri) and Pet/mrimentioning
confidence: 99%